Role of pH on zinc oxide nanoparticles synthesis using gum arabic for sustainable and safe antibacterial agent - Norlin, Pauzi; Norashikin, Mat Zain; Nurul Amira, Ahmad Yusof (Penerbit UMT, 2019)
In this study, ZnO nanoparticles were produced via the precipitating method supplemented by the microwave heating method. Zinc nitrate, sodium hydroxide and gum arabic were used as zinc salt, reducing agent and stabilizing agent respectively. The objective of this work is to investigate the pH effect, ranging from 5 to 12 on the ZnO nanoparticle size. By using Dynamic Light Scattering (DLS) method, the average nanoparticle size ranged from 200 nm to 350 nm was obtained. UV-vis absorption spectrum was found in the range of 340 nm – 350 nm indicating the absorption peak of ZnO nanoparticles. FTIR spectra showed peaks range from 412 to 466 cm-1 which indicating standard of Zn–O stretching. The presence of (100), (002) and (101) planes were apparent in the XRD result, indicating the crystalline phase of ZnO nanoparticles. At the pH < 7, zinc nitrate hydroxide hydrate was produced, which was similar to ZnO nanoparticle that is in white solution. pH 10 was required to attain the pure phase of ZnO nanoparticles. Smaller nanoparticles synthesized at pH 10 show larger antibacterial effects at both Gram-positive bacterium, Staphylococcus aureus and Gram-negative bacterium, Escherichia coli.